Designing an Educational Mentoring Model in Line with the Professional Development of Female Primary School Teachers with a Fuzzy Logic Approach - Morteza Hazrati; Sevda Sheikhi Lisar; Mohammad Taghipour (International Journal of Education Sciences, 2024)
The teacher is one of the most important elements known to have a close relationship with students and develop their various talents. If a teacher steps into the education scene with a new, creative and well-equipped attitude, he will naturally deliver capable, creative and new-thinking students to face life wisely and solve the problems of the human world. Therefore, the main goal of this research is to design an educational mentoring model in line with the professional development of female primary school teachers with the help of fuzzy logic. Since the current research seeks to design an educational mentoring model in line with the professional development of female primary school teachers and wants to provide reliable guidelines to policy makers to take corrective measures, it is considered applied research. However, this research also has a fundamental orientation given the knowledge gained from designing the educational mentoring model in accordance with the professional development of female primary school teachers and studying the effects of its effective variables. Because the research implementation technique is qualitative in nature, this essay takes an inductive approach to its analysis. Since the current research is among qualitative research, qualitative research strategies have been used in its conduct. The qualitative strategy used in the first stage of the research is grounded theory. The participants in this research were selected from experienced teachers, retired teachers, officials and managers of the field of education in the country. Snowball sampling was utilized in the initial phase of the study to conduct sampling. Finally, according to the use of foundation data method and finally fuzzy logic analysis, a paradigm model on teachers' educational mentoring has been designed.
Keywords: Educational Mentoring; FUZZY LOGIC; Organizational Learning; Professional Development; Teachers